Performance assessment of an R290 air conditioning system using hybrid ZnO–SiO₂ nanolubricant - Agung Nugroho; Tabah Priangkoso; Muhammad Alaik Amirullah; Indah Hartati; Fatna Nur Hidayah; Kofi Ampomah Benefo (Politeknik Negeri Lhokseumawe, 2026)
This study investigates the performance of a split air conditioning system using hybrid ZnO–SiO₂ nano lubricant with R290 refrigerant. Experiments were conducted under steady-state conditions at an ambient temperature of 27 ± 1°C with a constant cooling load. Nano lubricant concentrations of 0.18%, 0.36%, 0.91%, 1.79%, and 2.67% by mass were prepared using a two-step dispersion method involving mechanical stirring and ultrasonic agitation. System performance was evaluated based on energy consumption and Coefficient of Performance (COP). The results show that the addition of ZnO–SiO₂ nano lubricant improves system performance at optimal concentrations. The highest performance was observed at concentrations of 0.36% and 0.91%, resulting in an energy consumption reduction of approximately 9.7% compared to pure lubricant. The maximum COP value of 2.77 was obtained at a concentration of 0.91%. However, further increases in nanoparticle concentration led to performance degradation due to increased viscosity and particle agglomeration, which negatively affected compressor work and heat transfer. These findings indicate that the application of ZnO–SiO₂ nano lubricant can enhance the energy efficiency of air conditioning systems when applied at optimal concentrations.